Assessment of Carbon Neutrality and Sustainability of KCAET Campus in Kerala, India - Gopika, P. D.; Gayathri, Menon T.; Kumar, Suraj; Deepak, Anusree K.; Varughese, Anu; M. R. , Namitha (International Journal of Bio-resource and Stress Management, 2024)
The study was conducted during 2021–22 with a view to analyze the carbon neutrality and sustainability of Kelappaji College of Agricultural Engineering and Technology (KCAET) campus. It was done for proposing and implementing sector-wise adaptation and mitigation strategies to develop KCAET campus of Malappuram district in Kerala as a “Carbon Neutral Campus”. A carbon emission and sequestration analysis in the sectors of food consumption, transportation, energy, waste and AFOLU (Agriculture, Forest and Other Land Use) was done. The required data were obtained by conducting various surveys, and the corresponding emission factors were taken from available literatures. Carbon emission and sequestration of each sector was calculated as the product of the emission factor and activity data. The total carbon emission from the campus was found to be 522.086 CO2 eq.t and the total sequestration from the campus was 177.2 CO2 eq.t. Since the carbon emission is higher than carbon sequestration, it can be inferred that the campus is not carbon neutral. Strategies for achieving and maintaining carbon neutrality through reduction in emissions, improving stock of carbon and creating carbon credits/reserves need to be adopted. Since the major emission is from transportation and use of fuels, energy efficient methods to save energy and switching to renewable energy sources to bring down the emissions from energy consumption need to be implemented.